Drosophila PLP assembles centriolar-clouds that promote centriole stability, cohesion and MT nucleation - Roque, H; Saurya, S; Pratt, M; Johnson, E; Raff, J (Public Library of Science, 2018)
Pericentrin is a conserved centrosomal protein whose dysfunction has been linked to several human diseases. It has been implicated in many aspects of centrosome and cilia function, but its precise role is unclear. Here, we examine Drosophila Pericentrin-like-protein (PLP) function in vivo in tissues that form both centrosomes and cilia. Plp mutant centrioles exhibit four major defects: (1) They are short and have subtle structural abnormalities; (2) They disengage prematurely, and so overduplicate; (3) They organise fewer cytoplasmic MTs during interphase; (4) When forming cilia, they fail to establish and/or maintain a proper connection to the plasma membrane—although, surprisingly, they can still form an axoneme-like structure that can recruit transition zone (TZ) proteins. We show that PLP helps assemble “pericentriolar clouds” of electron-dense material that emanate from the central cartwheel spokes and spread outward to surround the mother centriole. We propose that the partial loss of these structures may largely explain the complex centriole, centrosome and cilium defects we observe in Plp mutant cells.